Strengthening the Production Quality System Through the Implementation of Quality Control in the Nila Tofu Factory - Stevanus Henry Delano; Kartika Yuliari; Sudjiono Sudjiono; Budi Heryanto (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Effective quality control is a key element in maintaining competitive advantage in the food industry, especially in tofu production at the Nila Tofu Factory. This study aims to analyze the implementation of quality control in improving the quality of tofu products, focusing on technical and managerial factors. The implementation of quality control methods, such as Statistical Quality Control (SQC), Taguchi, and Six Sigma, has proven effective in identifying and reducing product defects in several tofu factories. However, this study also shows that human factors, employee motivation, and suboptimal managerial systems are the main obstacles in maintaining consistent product quality. The results of the study through interviews with the owner and employees of the Nila Tofu Factory revealed a decline in product quality, especially in terms of inconsistent texture, as well as constraints on equipment and quality control that are not well structured. Proposed improvements include the procurement of new machines, routine training, providing results-based incentives, and the implementation of clear and standardized standard operating procedures (SOPs). This study suggests the importance of integration between technical and managerial systems to ensure sustainable quality control and increase the competitiveness of tofu products in the market